Demonstration Method: Shalat Practices for MDTA Students - Imron Julianto; Nanda Nur Alfiah; Sri Nurlaeli; Imam Tabroni (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this writing is to improve shalat skills in early childhood. Movement and shalat readings are practiced using demonstration methods with rigorous experimentation. This research was conducted in class 2 of MDT Nurul Fatah Islamiyah Kadumekar Purwakarta which consisted of 28 students. Classroom action research uses experimental methods by treating the experimental class and comparing it with the control class. The different test uses a t-test of two related samples. The practice of shalat is carried out using the demonstration method. Before this treatment was carried out, students were still not able to practice reading and shalat movements properly. Nearly 20 students are still not able to read the obligatory readings in shalat such as reading surah al-Fatihah properly, reading tasbih when bowing and prostrating, and reading tasyahud at the beginning and end. In the shalat movement also looks still not perfect. Ruku movements that are still less inclined and not tuma`ninah. Likewise with other movements. After the treatment was carried out, around 25 students were able to practice reading and shalat movements well. There are 3 students who are still not optimal due to other factors such as difficulties in reciting the Qur'an.